A Case on Remote Supervised Exam Practices During the Pandemic - Esra Pınar Uça Güneş; Nuray Gedik; Mehmet Ali Işıkoğlu; Barış Yiğit; İhsan Güneş; Ayfer Beylik (Open Praxis)
The primary objective of this manuscript is to examine the online assessment and exam security procedures during the pandemic, with a particular focus on higher education. In this context, the study investigates the measures employed by instructors, the challenges they encountered, and the strategies they employed to overcome these challenges in a higher education institution. To this end, a case study was conducted, employing a mixed research approach and utilizing both quantitative and qualitative data obtained through a questionnaire. The study group consisted of 163 instructors who provided distance education during the pandemic and volunteered to participate in the study. The findings have shown that the measures were largely contingent on the capabilities of the Learning Management System (LMS) in use. It was emphasized that students should be informed before the exam, that the appropriate exam duration and technical infrastructure conditions should be determined, and that accessibility should be ensured. The results highlight the necessity for the development of policies to address ethical concerns and the suggestion of standardizing the use of cameras in online exams. For more generalized results and recommendations, longer-term studies can focus on synthesizing the experiences and opinions of different stakeholders.